Design of Low Flow Undershot Type Water Turbine - E. Y. Setyawan; S. Djiwo; D. H. Praswanto; P Suwandono; P. Siagian (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Many water sources around us which have kinetic energy to run waterwheels are not optimally utilized. This energy can be converted into an energy source that can produce electricity. Therefore this study produced a design of a waterwheel that could be used in low-flow rivers to produce electricity by adding generators. Waterwheel modeling using Ansys is calculated based on flow assumptions. Modeling using this system provides advantages in the form of computational power efficiency, the stability of numerical calculations and the accuracy of the resulting solutions. Numerical analysis of the waterwheel is assumed that the waterwheel is half floating on the surface of the water. As stated in the limitation of the problem that the incoming water flowing at a speed of 5 m/s from the flow moves the wheel. The flow rate of water that hit the blade on the waterwheel causes the waterwheel to rotate which is pressured by the flow of water with a number of 12 blades. With a relatively simple design, the waterwheel produces a wheel rotation I of 91 Rpm and II of 78 Rpm, with a torque of 39.2 N by using some analysis of this design can be applied to river flow with low flow velocity. The relatively simple design makes it easy to be produced and maintenance. River flow used is in the Malang District with a flow velocity of 1 m/s gets a power of 1128 W on waterwheel I while on waterwheel II gets a power of 967 W.